THE REVITALISATION OF GOTONG ROYONG: COMMUNITY PARTICIPATION IN ENVIRONMENTAL RESTORATION TO COMMEMORATE THE 80TH ANNIVERSARY OF INDONESIA’S INDEPENDENCE IN RT 02/RW 08, JL. ARJUNA, LABUH BARU TIMUR VILLAGE, PEKANBARU, RIAU - Abdul Kudus Zaini; Cyintia Kumalasari; Zaenal Muttaqin (CV. Multi Kreasi Media, 2025)
Gotong royong represents a fundamental traditional value within Indonesian society, functioning as a means of grassroots empowerment and fostering social resilience. This community service initiative took place in RT 02/RW 08, Jl. Arjuna, Labuh Baru Timur Village, to commemorate the 80th anniversary of the Republic of Indonesia's Independence. The program aimed to involve residents actively in environmental restoration efforts. Community members collaborated to clean drainage systems and enhance public spaces, thereby promoting sustainable environmental practices and strengthening social cohesion within the neighborhood.